Determination of job stress levels of physical education and sport teachers - Herguner, Gulten; Yucel, Ali Serdar; Bal, Fatih; Ozpinar, Saliha; Yaman, Cetin; Korkmaz, Murat; Kuyucu, Mihalis Michael (Sielae & Univ Coruna, Fac Filologia, 2025)
This study investigates how the job stress levels of physical education and sport teachers vary according to gender, age, educational status and job position. Within the scope of the research, the data obtained from 520 teachers were used and the job stress questionnaire was evaluated under four main subheadings. The results of Bartlett's test and Kaiser-Meyer-Olkin (KMO) coefficient for the suitability of the data for factor analysis showed that the data were quite suitable for factor analysis; while the workload sub-heading explained the highest variance with 26.7%, skill use explained 14.2%, decision freedom explained 12.03% and social support explained 11.6% of the total variance. In the analyses based on gender differences, it was determined that male teachers had higher levels of workload stress, while female teachers had higher levels of skill use, decision freedom and social support stress. In the analyses conducted between age groups, no significant differences were found in the sub-dimensions. Similar results were obtained in the analyses conducted according to education levels. In the analyses conducted according to job positions, it was determined that administrators did not differ from non-administrators in all dimensions. These results show that it is important to customise job stress management strategies according to gender, age and job positions. It is emphasised that general stress management strategies should be developed to cover all demographic groups.
Determinación de los niveles de estrés laboral de los profesores de educación física y deporte
Keywords: sport; job stress; gender differences; education level